2019
DOI: 10.2147/rrtm.s199577
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictors of hookworm and <em>Opisthorchis viverrini</em> infection among adolescents in urban Laos: a cross-sectional study</p>

Abstract: Purpose: Infection with hookworm and Opisthorchis viverrini are serious health problems among children and adolescents in Laos. In this study, we demonstrated the factors related to hookworm and O. viverrini infection, including primary school health programs, among secondary school students in Vientiane city of Laos. Material and methods: A cross-sectional survey and stool examination were conducted among secondary school student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 31 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…Previous studies by Aggarwal et al (2017) and Chudthaisong et al (2015) reported that food-borne parasitic infections were correlated with a lack of FSM facilities and personal hygiene factors. Similar studies were documented by Lindahl et al (2015), Grundy-Warr et al (2012), and Yoshida et al (2019) showing that the significance of direct contact with FS was found to be an influential factor on the prevalence of liver fluke infections. The effects of unsafely-managed FS on the prevalence of diarrhea infections are presented in Figure 3.…”
Section: Effects Of Unsafely-managed Fs On Human Health Riskssupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies by Aggarwal et al (2017) and Chudthaisong et al (2015) reported that food-borne parasitic infections were correlated with a lack of FSM facilities and personal hygiene factors. Similar studies were documented by Lindahl et al (2015), Grundy-Warr et al (2012), and Yoshida et al (2019) showing that the significance of direct contact with FS was found to be an influential factor on the prevalence of liver fluke infections. The effects of unsafely-managed FS on the prevalence of diarrhea infections are presented in Figure 3.…”
Section: Effects Of Unsafely-managed Fs On Human Health Riskssupporting
confidence: 83%
“…Most cities in low and middle income countries face adverse public health effects due to inadequate fecal sludge management (FSM) practices. Despite the target of the Millennium Development Goals 7c (MDG 7c), which aims to improve access to water and sanitation by 2015, 85% of the world's total FS is directly discharged onto public areas without any treatment, causing environmental pollution and public health problems (Al-Mohammed et al, 2010;Yoshida et al, 2019). Unsafely-managed FS contains pathogens leading to significant fecal pathogen infections worldwide, especially among Southeast Asian nations such as Thailand, Myanmar and Cambodia.…”
Section: Introductionmentioning
confidence: 99%
“…Hygiene programs in the included studies were undertaken in Thailand (46), Lao PDR (33,34,47), and Vietnam (41)(42)(43), and aimed to educate individuals on handwashing, toilet use, and food preparation. While sanitation programs focused on conducting latrine surveys (47), installing latrines, and managing human and animal waste (41)(42)(43)46). In Lao PDR (34), the study highlighted that taeniasis/cysticercosis posters related to WASH were effective in increasing women's knowledge about the disease, but were not successful for children and men.…”
Section: Interventions Related To Improving Wash Practicesmentioning
confidence: 99%
“…6 A recent study in one secondary school in capital city of Laos, Vientiene, showed that the hookworm infection rate was 36% in students aged 10-18 years old. 7 The prevalence of STH infection cases is still believed to be high in several areas in Indonesia. STH infection were around 17% in school-age children in Central Sulawesi.…”
Section: Introductionmentioning
confidence: 99%